Investigating competitive advantage in industrial networks. (19th January 2011) - Huber, Gerhard; Nöhammer, Elisabeth; Stummer, Harald
The present paper illustrates the importance of inter-firm relations in innovation oriented networks of OEMs and semi-finished product suppliers. Particularly in the automotive industry, companies tend to reduce the number of their suppliers and bundle them into hierarchical supplier pyramids characterised by low trust. However, establishing knowledge-transfer routines regarding production processes within the network can stabilise buyer-supplier cooperation and counterbalance the power embodied by the central buyer. Beside (1) inter-firm knowledge-sharing routines, this case study also analyses another potential source of inter-organisational competitive advantages: (2) partner-specific absorptive capacity. Both can form the basis for firms to loosen the classical supplier pyramids, to collaborate as partners and share mutual product development processes.